2017
DOI: 10.1007/s00415-017-8651-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of myelin oligodendrocyte glycoprotein seropositive optic neuritis: a cohort study in Shanghai, China

Abstract: Qualitative and quantitative visual outcomes of Asian optic neuritis (ON) patients with seropositive myelin oligodendrocyte glycoprotein (MOG) antibodies remain unknown. We retrospectively evaluated a cohort of new-onset ON patients in Shanghai, China between January 2015 and December 2016. Serum MOG and aquaporin-4 (AQP4) antibodies were detected using cell-based assays, and patients were followed-up for at least 6 months. The clinical characteristics and optical coherence tomography (OCT) results were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 34 publications
8
46
1
Order By: Relevance
“…These studies are consistent in suggesting that a single ON episode in MOGAD probably is more benign regarding its effect on the retina than a single ON attack in AQP4 ab-positive NMOSD. This is in line with several other studies reporting a generally favorable outcome from ON in MOGAD; however, exceptions to this rule with poor outcome have also been published (293)(294)(295)(296). Interestingly, MOGAD patients seem to have better visual outcomes after ON than AQP4 ab-positive NMOSD despite similar severity of macular GCIPL thinning (297).…”
Section: Neuromyelitis Optica Spectrum Disorders (Nmosd)supporting
confidence: 89%
“…These studies are consistent in suggesting that a single ON episode in MOGAD probably is more benign regarding its effect on the retina than a single ON attack in AQP4 ab-positive NMOSD. This is in line with several other studies reporting a generally favorable outcome from ON in MOGAD; however, exceptions to this rule with poor outcome have also been published (293)(294)(295)(296). Interestingly, MOGAD patients seem to have better visual outcomes after ON than AQP4 ab-positive NMOSD despite similar severity of macular GCIPL thinning (297).…”
Section: Neuromyelitis Optica Spectrum Disorders (Nmosd)supporting
confidence: 89%
“…Of these, 202 articles were selected and assessed for eligibility at the full-text level. After careful evaluation, 35 studies were included that met the inclusion criteria ( 8 , 29 , 30 , 33 , 36 , 39 , 41 , 45 , 47 , 48 , 51 – 54 , 57 , 59 , 63 , 65 , 66 , 68 , 69 , 71 , 72 , 74 85 ). The detailed flow chart is presented in Supplementary Figure 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Two other studies demonstrated, however, that the retinal neuro-axonal damage measured after an acute optic neuritis in patients who were MOG ab + was as severe as in patients with AQP-4 ab + NMO, suggesting that an equal deficit can remain from individual relapses in patients who are MOG ab + . 92 94 Due to the small number of cases, the therapeutic response of MOG ab associated CNS diseases is not well known. Most patients are treated with classical immunosuppressants like azathioprine.…”
Section: Mog Antibody Associated Cns Demyelinationmentioning
confidence: 99%